Mid term report (1997-1998): Testing Criteria and Indicators for the Sustainability of Tropical Forest Plantations in Indonesia - Purnadjaja (Center for International Forestry Research, 1998)
The listing presented is based on subjective analysis of the content of the two sets of C&I. This analysis will be reviewed at a workshop on this subject Friday, 20 March 1998. It is our expectation that subsequent to the workshop the list would be finalised. Looking at the differences in term of location and team composition, a simple comparison seems difficult. The CIFOR C&I Guidelines were useful for each scientist to familiarise themselves with the methods and C&I in general. But both teams had to modify and adapt the procedures. There were discrepancies between the Form 1 exercise, in most cases, and the subsequent Form 2 exercise. The more crucial problem was ensuring inter-disciplinary and team work during the field evaluations based on Form 2. The experts tended to evaluate just their own "specialised list", refraining from assisting in the evaluation of their team mates lists. Thus in constructing the "final" list more redundancies that necessary remained. The other "handicap" faced by the experts is that because the research C&I for Plantation Forests is a 'first' by CIFOR, there were no existing 'base sets' of C&I available for the teams to test. Instead they had to develop C&I based on the existing sets of "guidelines" for good plantation management. Both team used only two main such guidelines (ITTO and WWF/IUCN), defining their own Principles, Criteria and Indicators based on them. These were then evaluated on Form 1 and transferred to Form 2 if found acceptable. The forthcoming tests of plantation forest C&I in Indonesia will however be based mainly on the results of the Riau and Subanjeriji exercises, drawing on the guidelines from ITTO and WWF/IUCN only as resource material. This should improve the efficincy of the testing exercise. In general, the Riau team may have given too much attention to detail, entering the level of 'verifiers' instead of staying with indicators. In the forthcoming tests it will be important to keep in mind the need to move towards a 'minimum set' of C&I in order to reduce the cost and tendium of an assessment or monitoring exercise.. It will also be important that more time is allocated for the testing in future tests. We anticipate increasing the number of days available for testing by at least two.